Complicaciones del manejo quirúrgico tardío de la colecistitis aguda en el Hospital Manuel Ygnacio Monteros en periodo enero - junio 2016. - Mosquera Carrión, Diego Alexander (2017)
A prospective, descriptive, transversal field study was conducted in a population of 55 patients, of both genders where women predominated with 69.09% (n = 38) with an average age between 30 to 40 years it represents 30, 91% of the study population, with a diagnosis of acute cholecystitis who entered the Emergency Service Hospital Manuel Ygnacio Monteros city of Loja during the period from January to June in 2016. the review and data collection was taken from the medical history in the AS400 system; The general objective was: Determine Late complications Surgical Management of acute cholecystitis; And the overall objectives were to identify what the common complication, management of acute cholecystitis; Knowing the surgical technique most commonly used by type of complication and establish the use of the Guidelines Consensus Tokyo 2007 in the management of acute cholecystitis. The data were tabulated and analyzed using Microsoft Excel 2010 program the total cases (n = 55) was observed that 38.18% (n = 21) presented as a frequent complication of acute cholecystitis in patients intervened belatedly followed the Hidrocolecisto Piocolecisto representing 18.18% (n = 10), 96.36% (n = 53) were resolved by laparoscopic surgery and only 3.64% (n = 2) were resolved by conventional surgery corresponding to drilling vesicular and pancreatitis. And according to the distribution of complications based Consensus guides Tokyo 2007 Grade II was the most used and represents 61.82% (n = 34). So we conclude in this study the importance of an early resolution of the acute cholecystitis to avoid complications that increase morbidity and mortality. Keywords: Complications, Late Surgical Management, Acute Cholecystitis, Tokyo Consensus